Reconciliaciones y estrategias de oferta en el mercado mayorista de electricidad de Colombia; Reconciliations and bid strategies in the Colombian wholesale electricity market - Jaime Carabalí; Alex Pérez; Luis Ángel Meneses Cerón; Libardo Rojas (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– In this paper, we study the relationship between reconciliations in the Colombian electricity market and the bid prices by firms on the spot market. In this work,we propose a model of behavior of the firm to elaborate theoretical predictions about the relationship between the reconciliations and the bid prices. Subsequently, we developed an empirical strategy to test the predictions of our model. We find that when firms expect their units to have negative reconciliations the next day, they tend to reduce the bid prices for their units. To positive reconciliations, there is no evidence of any relationship.
Keywords: D44; D43; D22; C72; L13; 330; electricity market; spot market; bid strategies; reconciliations